Exploring the Use of Real-Time Location Systems (RTLS) to Improve Warehouse Management - Kansith, Chanin; Pongsathornwiwat, Akkaranan; Dusadenode, Siwiga (Journal of Applied Statistics and Information Technology, 2024)
This research investigates the application of Real-Time Location System (RTLS) technology for enhancing warehouse management efficiency. The study was conducted in two phases. The first is Experimental Design and Data Collection within a Smart Logistics Laboratory: Various scenarios were simulated to assess the impact of RTLS on congestion patterns. The collected data was subsequently analyzed and utilized to improve workflow through simulations incorporating the Traveling Salesman Problem (TSP) Strategy model. The second is Queuing Analysis and Layout Optimization. It proposes to identify Bottlenecks within the warehouse were identified through queuing analysis, and warehouse layouts were redesigned to optimize operational processes. The results of the experiment demonstrate the efficacy of applying RTLS data to significantly improve warehouse management efficiency. For instance, the analysis of RTLS data facilitated the identification of congestion issues, which led to the development of multiple scenario simulations and the implementation of efficient space utilization strategies. Additionally, the acquired data was utilized in simulations to ascertain optimal solutions for enhancing warehouse workflow. A primary limitation of this research was the constraint imposed by limited space. Consequently, future research should consider utilizing actual warehouse spaces and processes to thoroughly evaluate the potential benefits of RTLS implementation.